Anti‐hypertensive use for non‐severe gestational hypertension in Botswana: A case‐control study. Issue 3 (17th July 2021) - Johnson, Katherine M.; Zash, Rebecca; Modest, Anna M.; Luckett, Rebecca; Diseko, Modiegi; Mmalane, Mompati; Makhema, Joseph; Ramogola‐Masire, Doreen; Wylie, Blair J.; Shapiro, Roger
Abstract: Objective: The fetal risks and benefits of antihypertensives to treat gestational hypertension in pregnancy are understudied, particularly in low‐ and middle‐income countries. Methods: We performed a nested case‐control study within a retrospective cohort of obstetrical patients in Botswana from 2014 to 2019. We included women carrying singletons who developed new onset non‐severe hypertension (140–159 mm Hg systolic or 90–109 mm Hg diastolic blood pressure) after 20 weeks of pregnancy. Cases were defined as women with either small‐for‐gestational‐age (SGA) infants or stillbirth, analyzed separately; controls were otherwise similar women without the adverse outcome in each analysis. Results: We identified 1932 cases of SGA (7925 controls) and 316 cases of stillbirth (9619 controls). Cases with SGA were more likely to have used an anti‐hypertensive than controls (33% vs 29%, adjusted odds ratio [aOR] 1.28, 95% confidence interval [CI] 1.15–1.43). Cases with stillbirth were more likely to have used an anti‐hypertensive than controls (42% versus 29%, aOR 1.45, 95% CI 1.14–1.83). Conclusion: Anti‐hypertensive use for new‐onset gestational hypertension was associated with an increased risk of having an SGA infant or a stillbirth among women who never developed severe hypertension. These data support conduct of a randomized clinical trial to determine the appropriate use of anti‐hypertensives in non‐severe gestational hypertension. Abstract : In an observational study of new‐onset, non‐severe hypertension in pregnancy in Botswana, anti‐hypertensive use was associated with small‐for‐gestational‐age infants and stillbirth.